The Influence of Internal Audit Roles, Leadership Styles and Compensation Levels on the Effectiveness of the Internal Control System - Ni Kadek Yuta Paramitha; Ni Luh Sari Widhiyani (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2026)
This study aims to determine the effect of the role of internal audit, leadership style and level of compensation on the effectiveness of the internal control system. This study uses a quantitative approach in the form of associative causality. This research was conducted at BPRs in Denpasar City with a total population of 20 BPRs. The sampling method used in this study is the total sampling method. The research data was collected using a questionnaire which was then analyzed by multiple linear regression analysis with the help of SPSS version 22 for windows. The results of the study stated that the role of internal audit, leadership style and level of compensation had a positive effect on the effectiveness of the internal control system at BPR in Denpasar City.